Global integriti and accountability a multilevel approach to ethical governance / Jamaliah Said - Said, Jamaliah (UiTM Press, 2024)
In the contemporary context of governance and ethics, the concepts of integrity and accountability have assumed a pivotal role in the functioning of organisations, governments, and societies at large. In the context of global community's ongoing efforts to address multifaceted challenges of an economic, social, and environmental nature, it is evident that there is a pressing need to establish robust frameworks for ethical governance. This chapter provides the basis for a comprehensive examination of these fundamental principles, offering an in-depth analysis of their significance, historical evolution, and indispensable role in sustainable development.